Sorghum in India with Special Refernce to Arid Zone - Mann, H S; Singh, Panjab (Annals of Arid Zone, 2016)
The hectareage, production and the average yields of sorghum (Sorghum Sorghum vulgare L.) in last two decades have been stated. Area, production and also the average yields recorded during the fifties and seventies are comparable. Over the base year of 1967-68, marked as the year of green revolution, the average hectareage in sorghum during 1968-75 decreased by 7.3% while the production by 16.9% inspite of 1.5% increased coverage under the hybrid varieties. During a decade of the green revolution (1967-75), the total production increased by 2.4% inspite of 2% decrease in total hectareage compared to those during a decade preceding the green revolution (1955-66). This increase was mainly for higher national productivity and total production in 67-68 and74-75. The average productivity of 500 Kg/ha attained in the late fifties remained more or less same in the sixties and decreased to around 450 Kg in early seventies. The existing varieties do have potentialities to yield many f9ld higher than those presently obtained but only under proper management conditions. In this paper it has been emphasised to allot priorities to increase in coverage under the high yielding varieties and their cultivation under suitable management conditions through massive extension programmes for an early increase in the total sorghum production in the country.